2012
DOI: 10.1152/ajprenal.00212.2012
|View full text |Cite
|
Sign up to set email alerts
|

Collagen VIII influences epithelial phenotypic changes in experimental diabetic nephropathy

Abstract: Epithelial-to-mesenchymal transition (EMT) is an important mechanism of renal tubulo-interstitial fibrosis in diabetic nephropathy (DN). Inducers of EMT, among others, are transforming growth factor-β1(TGF-β1) as well as extracellular collagens. In renal cells of diabetic mice and in kidneys of patients with DN, the expression of collagen VIII (gene: Col8α1/α2) is enhanced and characteristic features of DN in streptozotocin (STZ)-induced diabetic Col8α1/α2 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 86 publications
0
33
0
Order By: Relevance
“…Even though we used a high dose of STZ (delivered as a single intraperitoneal injection of 150 mg/kg) to establish the diabetic model, our investigations were carried out at 3 and 6 months after the STZ administration; this strategy minimized the potential role of tubular toxicity, but did not eliminate it. Establishing the model by using a repeated injection of low dose STZ (50 mg/kg/day × 5 days) would have been more appropriate [48], and future studies should consider this modeling approach. Second, the STZ-induced diabetes model was established in C57BL/6J mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we used a high dose of STZ (delivered as a single intraperitoneal injection of 150 mg/kg) to establish the diabetic model, our investigations were carried out at 3 and 6 months after the STZ administration; this strategy minimized the potential role of tubular toxicity, but did not eliminate it. Establishing the model by using a repeated injection of low dose STZ (50 mg/kg/day × 5 days) would have been more appropriate [48], and future studies should consider this modeling approach. Second, the STZ-induced diabetes model was established in C57BL/6J mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal deposition of ECM is one of the main pathological changes observed following UUO, and leads to a decrease in the diffusion of oxygen (23). It also contributes to abnormal intercellular signaling, leading to a vicious cycle of ECM deposition (24,25). In the present study, Masson’s trichrome staining revealed that small quantities of ECM were present in the normal kidneys, predominantly in the glomerular basement membrane and the peritubular blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Previous studies have reported an inverse correlation between the number of myofibroblasts and renal function in DN patients. During the pathological process, extracellular matrix (ECM) proteins, including a variety of collagens, laminin and fibronectin (FN), accumulate in the mesangium and renal tubulointerstitium, therefore leading to glomerulosclerosis and interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Previous studies have reported an inverse correlation between the number of myofibroblasts and renal function in DN patients. 2,4,6,9,10 Podocytes, glomerular epithelial cells, are the sites of one of the origins of matrix-producing myofibroblasts among the bone marrow, tubular epithelium, and vascular endothelium in the diseased kidney. As a source of matrixgenerating fibroblasts, the renal epithelial-to-mesenchymal transition (EMT) has attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%